2016
DOI: 10.1175/jcli-d-15-0630.1
|View full text |Cite
|
Sign up to set email alerts
|

Zonal Variations in the Southern Ocean Heat Budget

Abstract: The spatial structure of the upper ocean heat budget in the Antarctic Circumpolar Current (ACC) is investigated using the ⅙°, data-assimilating Southern Ocean State Estimate (SOSE) for 2005–10. The ACC circumpolar integrated budget shows that 0.27 PW of ocean heat gain from the atmosphere and 0.38 PW heat gain from divergence of geostrophic heat transport are balanced by −0.58 PW cooling by divergence of Ekman heat transport and −0.09 PW divergence of vertical heat transport. However, this circumpolar integrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
58
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(73 citation statements)
references
References 50 publications
8
58
0
Order By: Relevance
“…While most of the studies focus on the eddy vertical velocity variability induced by frontal instabilities and interactions with the bottom topography, these mean adiabatic vertical fluxes may have an impact on the nutrient fluxes into the euphotic layer and on the mean air‐sea heat fluxes. While this will merit dedicated investigations with longer time series, we note here that the patterns of the vertical velocities in Figure closely remind the residual between the ageostrophic transport and the Ekman transport in Tamsitt et al (). This implies that our purely observation‐based reconstructions are in good agreement with Southern Ocean State Estimate (SOSE).…”
Section: Discussionsupporting
confidence: 75%
“…While most of the studies focus on the eddy vertical velocity variability induced by frontal instabilities and interactions with the bottom topography, these mean adiabatic vertical fluxes may have an impact on the nutrient fluxes into the euphotic layer and on the mean air‐sea heat fluxes. While this will merit dedicated investigations with longer time series, we note here that the patterns of the vertical velocities in Figure closely remind the residual between the ageostrophic transport and the Ekman transport in Tamsitt et al (). This implies that our purely observation‐based reconstructions are in good agreement with Southern Ocean State Estimate (SOSE).…”
Section: Discussionsupporting
confidence: 75%
“…Radko and Marshall (2006) appreciated that zonal variations in this surface buoyancy flux could locally influence the strength of overturning, but recent studies have shown that transitions in the surface buoyancy flux may be more abrupt than a simple sinusoid with the gravest wavenumber (Cerove cki et al 2011;Bishop et al 2016). In particular, Tamsitt et al (2016) show that while there is a large discrepancy in the surface heat flux across different basins, the intrabasin heat flux is largely uniform. This result is consistent with the models derived here in that modifications to the surface buoyancy flux are largely related to changes in the outcrop position across different basins to accommodate zonal convergence/divergence in the ACC.…”
Section: Discussionmentioning
confidence: 92%
“…Available air-sea buoyancy flux products (Large and Yeager 2009;Cerove cki et al 2011) show large-scale, zonally asymmetric patterns with buoyancy gain in the Atlantic and Indian Oceans (outside of the Agulhas Retroflection) and weaker buoyancy fluxes (both positive and negative) in the Pacific. Tamsitt et al (2016) have analyzed the surface heat budget in the Southern Ocean State Estimate (SOSE) model and showed that topographic steering and zonal asymmetry in air-sea exchange leads to even more dramatic zonal variability in the surface heat flux. In one of the only studies to address the dynamics of this zonal structure, Radko and Marshall (2006) introduced a perturbation with a mode-1 zonal wavenumber to the zonally averaged properties of the ACC.…”
Section: Fig 2 (Left)mentioning
confidence: 99%
See 1 more Smart Citation
“…All regions had latitudes between 77°S and 30°S. The subdivision of SO into the three main oceanic basins corresponds to important zonal differences in the ACC flow and SO physics (e.g., Tamsitt et al, ).…”
Section: Data Theory and Methodsmentioning
confidence: 99%